Cell Plasticity-Related Phenotypes and Taxanes Resistance in Castration-Resistant Prostate Cancer - Jiménez, Natalia; Reig, Òscar; Montalbo, Ruth; Milà-Guasch, Maria; Nadal-Dieste, Lluis; Castellano, Giancarlo; Lozano, Juan José; Victoria, Iván; Font, Albert; Rodriguez-Vida, Alejo; Carles, Joan; Suárez, Cristina; et al. (Frontiers in Oncology, 2020)
The prostatic tumor cells plasticity is involved in resistance to hormone-therapy, allowing these cells to survive despite androgen receptor inhibition. However, its role in taxanes resistance has not been fully established. Gene expression of plasticity-related phenotypes such as epithelial-mesenchymal transition (EMT), stem cell-like and neuroendocrine (NE) phenotypes was studied in vitro, in silico, in circulating tumor cells (CTCs) (N=22) and in tumor samples (N=117) from taxanes-treated metastatic castration-resistant prostate cancer (mCRPC) patients. Docetaxel (D)-resistant cells presented a more pronounced EMT phenotype than cabazitaxel (CZ)-resistant cells. In silico analysis revealed ESRP1 down-regulation in taxane-exposed mCRPC samples. Cell plasticity-related changes occurred in CTCs after taxanes treatment. Tumor EMT phenotype was associated with lower PSA progression-free survival (PFS) to D (P<0.001), and better to CZ (P=0.002). High ESRP1 expression was independently associated with longer PSA-PFS (P<0.001) and radiologic-PFS (P=0.001) in D and shorter PSA-PFS in the CZ cohort (P=0.041). High SYP expression was independently associated with lower PSA-PFS in D (P=0.003) and overall survival (OS) in CZ (P=0.002), and high EZH2 expression was associated with adverse OS in D-treated patients (P=0.013). In conclusion, EMT profile in primary tumor is differentially associated with D or CZ benefit and NE dedifferentiation correlates with adverse taxanes clinical outcome.